Birth Centre versus delivery room - the relationship between place of birth and experience of childbirth - Grażyna Bączek; Sylwia Rychlewicz; Tomasz Duda; Anna Kajdy; Dorota Sys; Barbara Baranowska (University of Ostrava, 2019)
Aim: Satisfaction with medical care is an important element of birth experience. The aim of this study was to attempt to assess the effect of location (birth centre and delivery room) on the experiences and opinions of labouring women concerning childbirth. Design: Cross-sectional study. Methods: Two hundred women after childbirth participated in surveys, which were conducted one-four days after childbirth. The research tools used were the authors' own survey questionnaire and a standardised tool: the Inventory to Measure Coping Strategies with Stress - Mini-Cope. Results: Women who gave birth at the birth centre more often considered that the delivery had met their expectations. Both the women who gave birth to children at the birth centre and those who gave birth in the delivery room wanted to have their next childbirth in the same place. Women who underwent childbirth at a birth centre rated the experience more highly than women who experienced childbirth in a delivery room, and also managed stress better during childbirth. Conclusion: Women who chose to have their birth at a birth centre and, thus, to experience it more fully, more often stated that the childbirth had met their expectations. They managed stress better during childbirth and gave significantly better assessments of the experience of childbirth.